Collaborative analysis of student work : improving teaching and learning - Langer, Georgea M., 1948-; Colton, Amy B., 1954-; Goff, Loretta S., 1953- (Alexandria, VA : Association for Supervision and Curriculum Development, 2003)
Examines the benefits of collaborative analysis of student work and explains how teachers can set up an effective program within their schools.
Includes bibliographical references (p. 201-206) and index.
Professional
Keywords: Academic achievement -- United States -- Evaluation; Educational tests and measurements -- United States; Group work in education -- United States; Academic achievement -- United States -- Evaluation; Cooperative learning; Educational tests and measurements -- United States